TINJAUAN DESAIN KEMASAN PRODUK OLAHAN BELIMBING “RASA DEWA” - Dwi Ramayanti (Narada : Jurnal Desain dan Seni, 2022)
An attractive packaging design will be an advantage of a product. Products will be more visually attractive and also attract the attention of buyers. Depok City is a city known for star fruit cultivation and has MSME products made from star fruit, however, many UMKM have been affected by the pandemic causing a decline in productivity.The research method used is qualitative with research instruments in the form of observation, interview guidelines, and researchers as key instruments. This research was conducted to review the packaging design of food products and starfruit-based drinks in Depok, brand Rasa Dewa with product variants such as juice, syrup and dodol. Specifically, it aims to determine the structural design and interface design of the packaging, in general, it aims to help improve the packaging design knowledge of these starfruit-based food and beverage producers. The expected benefit is that the packaging design will be better and as a literature study for other researchers.